(untitled) (Biological Sciences - PJSIR, 2008)
: In order to demonstrate the links between chemistry and biology, some biological properties of a few furanic compounds have been described, starting from the synthesis and the structural characteristics. Also some features of the furan compounds with oximes; semicarbazones and thiosemicarbazones have been pointed out